2019
DOI: 10.1080/0886022x.2019.1632718
|View full text |Cite
|
Sign up to set email alerts
|

Association between simple renal cyst and kidney damage in a Chinese cohort study

Abstract: Background: The presence of simple renal cyst (SRC) has been associated to renal dysfunction, but the results were inconsistent. Accordingly, we conducted a longitudinal cohort study to explore the association between SRC and kidney damage. Methods: A total of 4274 adults (aged 45.4 ± 13.6 years) without chronic kidney disease at baseline were enrolled in 2008. SRC was assessed by ultrasonography. Logistic regression analysis were applied to explore the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
1
16
1
Order By: Relevance
“…Logistic analysis showed that the SRC was associated with eGFR > 105.21 ml/min/1.73 m 2 , even after adjusting for confounders. A study in a healthy population with follow up data indicated that participants with SRC had a higher incidence of proteinuria and renal insufficiency, which was similar to our results (Chen et al, 2019). Due to age and renal function are closely related (O'Sullivan et al, 2017), we analyzed the renal function and SRCs after stratifying patients by age to address the potential confounding effect of age.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Logistic analysis showed that the SRC was associated with eGFR > 105.21 ml/min/1.73 m 2 , even after adjusting for confounders. A study in a healthy population with follow up data indicated that participants with SRC had a higher incidence of proteinuria and renal insufficiency, which was similar to our results (Chen et al, 2019). Due to age and renal function are closely related (O'Sullivan et al, 2017), we analyzed the renal function and SRCs after stratifying patients by age to address the potential confounding effect of age.…”
Section: Discussionsupporting
confidence: 85%
“…The risk of chronic kidney failure in patients with renal cysts is 1.5 times higher than that in patients without renal cysts (Al-Said and O'Neill, 2003). Studies in the Chinese population show that participants with SRC were more susceptible to proteinuria and renal insufficiency and that the maximum diameter of the cyst contributed to the decline in renal function (Kong et al, 2018;Chen et al, 2019). Based on these data, SRCs are common renal diseases that potentially result in a decrease in renal function.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, the current study had the largest SRC sample size in Chinese outpatients. We found higher rate of renal dysfunction compared with another Chinese research after follow-up (15.6% vs. 3.8%) [2]. Such difference may be related to the source of patients.…”
Section: Discussioncontrasting
confidence: 55%
“…It found allograft functions were both normal in cyst group and non-cyst group, but cysts in donor kidney could affect allograft function, and cystic donors had more sclerotic glomeruli than non-cyst group. Other researches declared that SRCs were associated with higher incidence of proteinuria, increased serum creatinine and decreased eGFR [2][3][4]. All the above showed negative effects of SRCs on renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation